Innocent frauds meet Goodhart's Law in monetary policy - Dirk Bezemer; Geoffrey Gardiner (Levy Economics Institute of Bard College, 2010)
This paper discusses recent UK monetary policies as instances of John Kenneth Galbraith's 'innocent fraud,' including the idea that money is a thing rather than a relationship, the fallacy of composition (i.e., that what is possible for one bank is possible for all banks), and the belief that the money supply can be controlled by reserves management. The origins of the idea of quantitative easing (QE), and its defense when it was applied in Britain, are analyzed through this lens. An empirical analysis of the effect of reserves on lending is conducted; we do not find evidence that QE 'worked,' either by a direct effect on money spending, or through an equity market effect. These findings are placed in a historical context in a comparison with earlier money control experiments in the UK.
Keywords: E52; E58; 330; quantitative easing; UK innocent frauds; accounting